A comparative study of Cyclofem® and depot medroxyprogesterone acetate (DMPA) effects on endometrial vasculature. Issue 4 (1st October 2007) - Simbar, Masoumeh; Zham, Hananeh; Tehrani, Fahimeh Ramezani; Hashemi, Zeinab; Fraser, Ian S
Abstract : Objectives: The most common reason for discontinuation of long-acting progestogen-only contraceptives is irregular bleeding following local endometrial vascular changes. To reduce unpredictable bleeding episodes among depot medroxyprogesterone acetate (DMPA) users, the combined injectable contraceptive, Cyclofem®, was offered as an alternative. However, there is a gap in our knowledge about the effects of Cyclofem on the endometrial vasculature and patterns of bleeding. This study aimed to compare the effects of Cyclofem and DMPA on endometrial vascular density, endometrial histology and pattern of bleeding. Methods: Sixty-eight healthy women with regular menstrual bleeding and seeking injectable long-acting contraceptives were recruited. Two endometrial samples (before and 3 to 6 months after initial exposure to DMPA or Cyclofem) were collected from each participant. The samples were stained using an immunohistochemical method and anti-CD34 to visualise the endometrial vasculature. Endometrial vascular density was assessed using standard techniques. Results: Sixty-eight women were randomly assigned to Cyclofem (38 women) or DMPA (30 women). Endometrial vascular density was 149.3 ± 6.7 (mean ± SD)/mm 2 before injection. This significantly decreased to 132.4 ± 12.2 after DMPA use, and from 151.9 ± 5.8 to 131.8 ± 12.8 vessels/mm 2 following Cyclofem use (paired t -test, p <0.05). However, there was no significant difference between endometrial vascular density during treatment with Cyclofem or DMPA. Total bleeding days in the first and second 3-month time intervals were 28 ± 23 and 18 ± 12 days in DMPA users and 22 ± 14 and 16 ± 9 days in Cyclofem users, respectively, Spotting was the most common type of bleeding experienced, and atrophic endometrium was the most common histological pattern observed in both groups. Conclusions: This study demonstrated that both Cyclofem and DMPA use are associated with decreased endometrial vascular density and atrophic endometrium, in addition to irregular bleeding, mainly spotting. There was no significant difference in bleeding patterns or endometrial findings observed for these two injectable contraceptives in Iranian women.